Analisis Yuridis Putusan Hakim Nomor 62/PUU-XXII 2024 Penghapusan Presidential Threshold - Putri Octaviani (Jurnal Hukum Lex Generalis, 2026)
This study aims to analyze the Constitutional Court Decision and its impact on the presidential election system in Indonesia. The researcher used a normative legal research method using a jurisprudential approach, a conceptual approach, and an analytical approach. Data were analyzed descriptively to obtain research results regarding the Presidential Threshold. The results of the Constitutional Court (MK) Decision Number 62/PUU-XXII/2024 tested the constitutionality of Article 222 of Law Number 7 of 2017 concerning General Elections which regulates the presidential threshold (threshold requirements for presidential and vice presidential nominations). In its decision read on April 29, 2024, the Constitutional Court stated that the presidential threshold provision was contrary to the 1945 Constitution and did not have binding legal force.